An unexpected association - cord hemangioma and patent urachus - Ana Lachado; Fábio Barroso; Rafael Brás; Maria do Céu Rodrigues; Ana Coelho; Ana Sofia Marinho; Fátima Carvalho; Elisa Proença; Céu Mota (Hygeia Press di Corridori Marinella, 2020)
A patent urachus is the presence of structures found early in pregnancy, which could be associated with other abnormality in 46% cases. Hemangiomas are benign tumors and are more common in the skin. Umbilical cord hemangiomas are very rare, with fewer than 50 cases described in the literature. Here we report a clinical case of a neonate with a prenatal diagnosis of an umbilical cord hemangioma and a patent urachus. We would like to draw attention to the differential diagnosis of cord masses, as well as to the importance of early diagnosis and the appropriate management of the newborn. To our knowledge, this is the first case reported of a newborn diagnosed with this association.